PENGARUH PROFITABILITAS DAN FREE CASH FLOW TERHADAP MANAJEMEN LABA RIIL DENGAN KUALITAS AUDIT SEBAGAI PEMODERASI (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BEI TAHUN 2019-2021) - Wahyuni, Wahyuni (Jurnal KIAFE, 2023)
This research aims to 1) test the effect of profitability on real earnings management 2) test the effect of Free cash flow on real earnings management 3) test the effect of profitability on real earnings management with audit quality as a moderator 4) to test the effect of Free cash flow on real earnings management with audit quality as a moderator. The population in this research are consumer goods sector companies listed on the Indonesia Stock Exchange in 2019-2021. The sample selection used a purposive sampling method to obtain 48 companies in the consumer goods sector. The research period was 3 years and 144 data were studied. This research uses panel data regression analysis and Moderated Regression Analysis (MRA). The selected panel data model is random effect followed by classic assumption tests, namely the normality test and multicollinearity test. The results of this research show that profitability has an insignificant positive effect on real earnings management. Free cash flow has a significant positive effect on earnings management. Audit quality can weaken the influence of profitability on real earnings management. On the other hand, audit quality can strengthen the influence of Free cash flow on real earnings management.